2022
DOI: 10.3389/fgene.2022.1038174
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer analysis of copper homeostasis-related gene lipoyltransferase 1: Its potential biological functions and prognosis values

Abstract: As a key copper homeostasis-related molecule, lipoyltransferase 1 (LIPT1) is an essential enzyme for the activation of mitochondrial 2-ketoacid dehydrogenase, participating in fatty acylation. However, the biological significances of LIPT1 in the pan-cancer are unclear. Here, we comprehensively analyzed the functional characteristics of LIPT1 in human cancers and its roles in immune response. We found that LIPT1 was down-regulated in some cancers. And LIPT1 overexpression is associated with favorable prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Emerging research has revealed that cuproptosis participates in the development and treatment of cancers and that an imbalance of copper homeostasis leads to cancer cell growth and migration [26] . In our research, we observed that most CRGs were differentially expressed between CRC and normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research has revealed that cuproptosis participates in the development and treatment of cancers and that an imbalance of copper homeostasis leads to cancer cell growth and migration [26] . In our research, we observed that most CRGs were differentially expressed between CRC and normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research has revealed that cuproptosis participates in the development and treatment of cancers and that an imbalance of copper homeostasis leads to cancer cell growth and migration [27] . In our research, we observed that most CRGs were differentially expressed between CRC and normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of LIPT-1 was associated with a favorable prognosis in patients with breast cancer, and it was also correlated with immune cell infiltration (B lymphocytes, fibroblasts, and CD8+ T lymphocytes) [128]. A role for LIPT-1 as a novel prognostic and immunologic biomarker in breast cancer has been proposed [128]. An analysis of the Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) 2000 dataset showed that patients with breast cancer with a high expression of the CRG SLC31A1 had a worse prognosis than those with a low expression of this CRG [130].…”
Section: Coppermentioning
confidence: 98%
“…The role of CRG LIPT1 in carcinogenesis was established in a 2022 study by Liu et al [128]. This gene encodes LIPT1, a lipoic acid-specific sequence enzyme responsible for maintaining the oxidative and reductive metabolism of glutamine [129].…”
Section: Coppermentioning
confidence: 99%
See 1 more Smart Citation